Spontaneous imbibition characteristics and influencing factors of shale oil reservoir in Qintong depression - Fengxia Li; Yuanyuan Li; Tong Zhou; Haibo Wang (Frontiers in Earth Science)
This study integrates one-dimensional and two-dimensional nuclear magnetic resonance (NMR) techniques to conduct spontaneous imbibition experiments on two distinct lithologies (laminated calcareous shale and bulk clay-rich shale) from the Qintong Depression using four different fluid types. Field emission scanning electron microscopy (FE-SEM) and computed tomography (CT) scanning were employed to observe and track the dynamic changes in shale microstructures at specific intervals allowing for a comprehensive analysis of induced microfractures and their propagation patterns. These methods enabled a deeper understanding of the underlying mechanisms, enriching the interpretation of the imbibition results. The study reveals that anionic surfactants demonstrate exceptional performance during the imbibition process, and the combination of surfactants further enhanced oil recovery. The imbibition process can be divided into three stages: the imbibition diffusion stage, the transition stage, and the equilibrium stage, with the diffusion stage serving as the primary contributor, driven predominantly by capillary pressure. The calcareous shale cores exhibited the highest imbibition rates in the early stages, approaching equilibrium in the middle stages. Conversely, the clay-rich shale cores maintained relatively high imbibition rates throughout the second stage, indicating different imbibition dynamics based on lithology. NMR, CT scanning, and SEM analysis highlighted significant lithology-dependent differences in the mechanisms driving induced microfracture development during the imbibition and hydration. In laminated calcareous shale, imbibition and hydration primarily proceeded through the dissolution of calcareous minerals, resulting in pore expansion and induced microfractures along pre-existing fractures. In contrast, clay-rich shale exhibited similar mineral dissolution but also experienced clay swelling due to its high clay content, leading to the formation of bedding-parallel fractures with distinct directional patterns along weak mineral-matrix bonds. The experimental results underscored the pivotal role of lithology in determining final imbibition efficiency, with high-clay-content shales demonstrating superior recovery rates under spontaneous imbibition conditions. This study provides critical experimental data and insights into the microscopic mechanisms governing spontaneous imbibition across varied lithologies and fluid types in the Qintong Depression. The results offer foundational knowledge for optimizing oilfield development strategies.